Remote teaching and eating disorders in nursing students during the Covid-19 pandemic - Oliveira, Ingrid de Carvalho; de Souza , Mirian Lopes; Messias, Cristhiane Maria Bazílio de Omena; Mendes, Marianne Louise Marinho (Seven Editora, 2023)
The context of the pandemic and the implementation of the remote teaching model brought changes to the usual lifestyle of most students. And in this way, inadequate eating behavior made nursing students susceptible to psychological eating disorders. Objective: to analyze the influence of remote teaching on the prevalence of the development of eating disorders (EDs) associated with image distortion in nursing students during the pandemic. Methodology: This is an observational, cross-sectional quantitative study with university students of the nursing course at the University of Pernambuco, located in the city of Petrolina, who were interviewed voluntarily in person. Eating behavior and image distortion were investigated using the Eating Disorder Examination Questionnaire (EDE-Q) and Silhouette Matching Task (STM) instruments, respectively. In addition, other data were collected from a sociodemographic questionnaire to verify the profile of the participants. Results: It was found that 92% of the evaluated students changed their eating habits after the pandemic, the majority being female. And that 48% of the students had positive results for the risk of developing ATs, and of these, 91% claim an increase in the frequency of key AT behaviors after experiencing remote teaching. Furthermore, it was observed that 85% of university students in the nursing course had alterations in their perception of body image. Conclusion: The statistical observational analysis carried out demonstrates that remote teaching implemented during the stress phase of the COVID-19 pandemic, influenced the increased risk of developing EDs and body dissatisfaction in students, reaffirming the need for preventive measures and awareness regarding the adoption of new teaching models. This emphasizes the importance of further studies on this issue. DOI:https://doi.org/10.56238/emerrelcovid19-032